Tail gut cyst: laparoscopic removal - a case report - Ghorpade, Niteen; Rahane, Tushar; Sharma, Rahul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
A tailgut cyst, also known as a retro rectal cystic hamartoma, is a rare, congenital cyst arising from remnants of the embryonic hindgut. We hereby presented a case report of a 53 years old lady who had undergone hysterectomy in 2010 and laparoscopic tailgut cyst removal in 2023 and came with backache and constipation since 1.5 years. She was thoroughly evaluated for the same and underwent magnetic resonance imaging (MRI) showing a well-defined multiloculated cystic lesion with no involvement of adjacent pelvic organs and sacral nerve roots. She underwent laparoscopic tailgut cystectomy. Postoperatively patient was relieved of her signs and symptoms.